Taufe und Typos Elemente und Theologie der Tauftypologien in 1.Korinther 10 und 1.Petrus 3 - Ostmeyer, Karl-Heinrich (Mohr Siebeck, 2000)
Baptism and Type. Elements and Theology of Baptism Typologies in 1 Corinthians 10 and 1 Peter 3. By Karl-Heinrich Ostmeyer.
PublicationDate: 20191210
Keywords: Taufe -- Neues Testament -- Array